To be a pilgrim: a comparative study of late medieval accounts of pilgrimage from Germany and England to the Holy Land - Boyle, M (2015)
As a large-scale international cultural phenomenon, the Jerusalem pilgrimage must be approached comparatively. This project compares the pilgrimage accounts of two Germans and two Englishmen who travelled to Jerusalem in the second half of the long fifteenth century. The texts are those of William Wey, (written c.1470), Bernhard von Breydenbach (printed 1486), Arnold von Harff (written 1499) and the Pylgrymage of Sir Richard Guylforde, composed by his anonymous chaplain (printed 1511). Each chapter focuses on a pilgrim, and one of four thematic topics: genre, the religious other, curiosity and print. This project treats these works as literary texts which can be approached from the perspective of cultural history, rather than as historical sources. The project, therefore, is more a consideration of how the pilgrimage is represented than it is about the events of each pilgrimage, and so it looks at the pilgrimages created in writing. Pilgrimage writings tend to focus on Jerusalem's spiritual significance, rather than its worldly position. In this sense, textual representations of travel to Jerusalem represent something of a disconnect with travel to other physical destinations, and the conceptual space of pilgrimage will be of key significance to this thesis. This has implications for practice as well as writing, and therefore the thesis will address how the writers consider their journeys, as well as the idea of virtual pilgrimage. The thesis engages with questions of identity, and how it is presented, as well as the authors' relationship with their audiences. This necessitates analysing collective identity, as well as the different audiences for printed and manuscript texts. The most important research question, bringing together these issues, considers whether the authors’ different geographical origins affect their self-presentation and understanding of pilgrimage. This leads to my central contention: that pilgrimage must be portrayed as a single, unified experience.